Evaluation of Implants, Clover, and Fescue Variety on Stocker Steers – Year 3 - Jaymelynn K. Farney; Larissa Muniz; Harley Allen (Kansas Agricultural Experiment Station Research Reports, 2023)
Sixty-four growing steers were used in a split-plot experiment, where the whole plot was pasture, and the split-plot was the implant level. Whole plot treatment was a 4 × 2 factorial with four levels of fescue (High Endophyte, Low Endophyte, Novel, or Endophyte Free) and two levels of legume (Legumes or No Legumes). The split-plot included four implant levels (No Implant, Synovex One Grass, Revalor-G, or Ralgro). Data collected were weights and ultrasound carcass characteristics when steers were coming off grass. Steers on High Endophyte had a lower average daily gain (ADG) and final weight than steers on novel endophyte, with those grazing pastures that had low endophyte and endophyte-free were intermediate. There was no difference in cattle gains or carcass measurements based on the addition of legumes or the type of implant the steers received. The drought restricted the days on grass and potentially reduced the positive effects of implants.
Keywords: fescue toxicity; growth; gain; endophyte-free; non-toxic; steers